2015
DOI: 10.1189/jlb.1a0914-459rr
|View full text |Cite
|
Sign up to set email alerts
|

Notch 1 and Notch 2 synergistically regulate the differentiation and function of invariant NKT cells

Abstract: Invariant natural killer T cells are a distinct subset of T cells that exert Janus-like functions. Moreover, Notch signaling is known to have critical roles in the development and functions of T cells. However, it is not known whether Notch signaling contributes to the development or functions of invariant natural killer T cells. Here, we found that CD4-specific gene ablation of Notch 1 and Notch 2 (N1N2(-/-)) increased the number of invariant natural killer T cells in the thymus but decreased them in the live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…The same study showed that NOTCH signaling was not essential for differentiation of CD24 + CD44 lo (stage 0) to CD24 lo CD44 + (stage 2/3) cells [156]. Conversely, mice with a conditional knockout of NOTCH1/NOTCH2 in CD4 + cells showed an impaired maturation of NKT cells from stage 2 NK1.1 2 CD44 + cells to stage 3 NK1.1 + CD44 + cells, indicating a requirement for NOTCH signaling in late NKT cell differentiation [157]. NKT cells in the spleen express NOTCH2 on the cell surface, and NKT cells in the liver express NOTCH1 and NOTCH2, indicating that mature/ peripheral NKT cells respond to intrinsic NOTCH signaling [157,158].…”
Section: Nkt Cellsmentioning
confidence: 91%
See 2 more Smart Citations
“…The same study showed that NOTCH signaling was not essential for differentiation of CD24 + CD44 lo (stage 0) to CD24 lo CD44 + (stage 2/3) cells [156]. Conversely, mice with a conditional knockout of NOTCH1/NOTCH2 in CD4 + cells showed an impaired maturation of NKT cells from stage 2 NK1.1 2 CD44 + cells to stage 3 NK1.1 + CD44 + cells, indicating a requirement for NOTCH signaling in late NKT cell differentiation [157]. NKT cells in the spleen express NOTCH2 on the cell surface, and NKT cells in the liver express NOTCH1 and NOTCH2, indicating that mature/ peripheral NKT cells respond to intrinsic NOTCH signaling [157,158].…”
Section: Nkt Cellsmentioning
confidence: 91%
“…Conversely, mice with a conditional knockout of NOTCH1/NOTCH2 in CD4 + cells showed an impaired maturation of NKT cells from stage 2 NK1.1 2 CD44 + cells to stage 3 NK1.1 + CD44 + cells, indicating a requirement for NOTCH signaling in late NKT cell differentiation [157]. NKT cells in the spleen express NOTCH2 on the cell surface, and NKT cells in the liver express NOTCH1 and NOTCH2, indicating that mature/ peripheral NKT cells respond to intrinsic NOTCH signaling [157,158]. Studies performed in vivo showed that NKT cells in the thymus and lymph nodes of mice with conditional knockout of NOTCH1/NOTCH2 in CD4 + cells displayed increased IL-17 expression upon a-GalCer challenge [157].…”
Section: Nkt Cellsmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, Notch1 and Notch2 play different roles in diabetic nephropathy (64). Nonetheless, the interaction between the two receptors can be synergistic: for example, in gut (65) and in immune cells (66). Thus, tissue context looks to be determining their individual roles.…”
Section: Discussionmentioning
confidence: 99%
“…Specific deletion of Notch 1 and Notch 2 in T cells affected the development of iNKT cells [62]. Several iNKT cell populations seemed affected, as increased numbers of stage 2 and 3 iNKT cells, increased proportion of iNKT17 and altered expression of PLZF in stage 1 iNKT cells was observed.…”
Section: Cell Intrinsic Signalsmentioning
confidence: 99%